Correlates of Food Insecurity Among Undergraduate Students - Bottorff, Joan L.; Hamilton, Casey; Huisken, Anne; Taylor, Darlene (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2020)
Food insecurity has been identified as an issue among postsecondary students. We conducted this study to describe the level of food insecurity in a sample of university students with a particular interest in the effect of marginalization. A cross-sectional survey was conducted using a volunteer sample of 3,636 undergraduate students (44% participation rate) at one [removed for blinding] university campus between February and May 2017. Forty-two percent (n=1479) of respondents were classified as experiencing food insecurity. Among those who were food insecure 58% (n=891) were female. Logistic regression analysis indicated that females, students living on campus, those with a diverseability (developmental, physical, or other diversability), individuals self-reporting as belonging to a visible minority and international students were more likely to experience food insecurity. When adjusted for sex, years on campus, and living situation, students who reported experiencing two or more forms of marginalization were 2.52 times more likely to be food insecure compared to students who do not report any form of marginalization. This study further supports concerns about high levels of food insecurity among university students in Canada. In particular, the findings highlight the risk for food insecurity among students who are already vulnerable to socio-economic inequity due to belonging to marginalized groups. Efforts to promote student wellbeing on university campuses need to address food insecurity by addressing system-level factors to equalize the field for all students at risk for food insecurity.